Does the selfish life-cycle model apply in the case of Japan? - Charles Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2020)
In this paper, we first provide a brief exposition of the simplest version of the selfish life cycle model or hypothesis, which is undoubtedly the most widely used theoretical model of household behavior in economics, and then survey the literature on household saving behavior in Japan (with emphasis on the author's own past research) to shed light on whether or not the selfish life-cycle model applies in the case of Japan. In particular, we survey the literature on the impact of the age structure of the population on the saving rate, the saving behavior of retired households, saving motives, the prevalence of bequests, bequest motives, tests of altruism, and the importance of borrowing (liquidity) constraints and show that almost all of the available evidence suggests that the selfish life-cycle model applies to a greater extent in Japan than it does in other countries. Finally, we discuss the policy implications of our findings.
Keywords: D11; D12; D14; D15; D64; E21; J14; 330; Age structure of the population; aged; altruism; bequests; bequest motives; borrowing constraints; consumption; dissaving; elderly; estates; household behavior; household saving; households; inheritances; intergenerational transfers; Japan; lifecyclehypothesis; life-cycle model; life-cycle theory; liquidity constraints; old age; retirees; saving; saving motives; selfishness